COST ANALYSIS OF BRANDED VERSUS GENERIC ANTI-DIABETIC DRUGS USED FOR THE TREATMENT OF TYPE 2 DIABETES MELLITUS IN A TERTIARY CARE HOSPITAL - SARANNYA RAVI; LIYA ROSLIN JOSEPH; SREELAKSHMI VENUGOPAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aims to assess the percentage cost variation among branded anti-diabetic drugs prescribed in a tertiary care hospital with its generic equivalent. Methods: A cross-sectional study was performed in a tertiary care hospital among 51 diabetic patients attending the endocrinology outpatient department. Demographic data and details of anti-diabetic drugs prescribed were collected from case sheets. Costs of branded anti-diabetic drugs were obtained from the current index of medical specialties April–July 2023 and their generic equivalents from Janaushadhi price list 2023. The percentage cost variation of these drugs per prescription was determined. Results: The mean age of the patients included in the study was 58.12, with 23 male and 28 female participants. Thirty-eight (74.5%) prescriptions contained oral hypoglycemic agent (OHA) alone, and 12 (23.54%) contained insulin and OHA. Metformin–glimepiride combination was the most common drug prescribed. The mean cost of the branded anti-diabetic drugs per prescription per day was 28.15±13.85 and the estimated mean cost of their generic equivalent was 12.10±6.68. A 135.61% cost variation was observed for the antidiabetic drug prescriptions studied. Conclusion: In this study, it was observed that there is a significant cost variation among branded and generic anti-diabetic drugs.